THE DEPRESSION OF THE FEMALE CHARACTER IN THE MOVIE “FATHERS AND DAUGHTERS” 2015 - Nurdianty, Nurdianty; Sunra, La (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research reveals the depression experienced by the female character in the movie